2020
DOI: 10.1016/j.micpath.2020.103998
|View full text |Cite
|
Sign up to set email alerts
|

Gga-miR-30d regulates infectious bronchitis virus infection by targeting USP47 in HD11 cells

Abstract: A B S T R A C TAvian infectious bronchitis virus (IBV) is a coronavirus which infects chickens and causes severe economic losses to the poultry industry worldwide. MicroRNAs (miRNAs) are important intracellular regulators and play a pivotal role in viral infections. In previous studies, we have revealed that IBV infection caused a significant downregulation of gga-miR-30d expression in chicken kidneys. In present study, we investigated the role of gga-miR-30d in the process of IBV infection of HD11 cell line i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
(36 reference statements)
0
21
0
1
Order By: Relevance
“…MicroRNAs (miRNAs), as 19-22 nucleotide non-coding RNAs, involve in multiple important biological processes by binding partially complementary sequences of its target gene mRNA 3'-untanslated region (3'-UTR) and repressing target gene functions. Many studies have demonstrated that miRNAs play important roles in resisting kinds of disease in birds, like Marek's disease virus, avian in uenza virus, bursal disease virus and others virus infection [6][7][8]. Our previous studies have also highlighted the critical role of miRNAs during MG-HS (Mycoplasma gallisepticum-Huangshi) infection in lung tissue of chicken embryo, including miR-19a, miR-130b-3p, miR-451 ect [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 88%
“…MicroRNAs (miRNAs), as 19-22 nucleotide non-coding RNAs, involve in multiple important biological processes by binding partially complementary sequences of its target gene mRNA 3'-untanslated region (3'-UTR) and repressing target gene functions. Many studies have demonstrated that miRNAs play important roles in resisting kinds of disease in birds, like Marek's disease virus, avian in uenza virus, bursal disease virus and others virus infection [6][7][8]. Our previous studies have also highlighted the critical role of miRNAs during MG-HS (Mycoplasma gallisepticum-Huangshi) infection in lung tissue of chicken embryo, including miR-19a, miR-130b-3p, miR-451 ect [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 88%
“…As a predicted DEmiRNA by sequence analysis, miR-146a-5p was also found to promote IBV replication of by targeting tumor necrosis factor receptor superfamily member 18 (TNFRSF18) and IL-1 receptor associated kinase-2 (IRAK2) [120]. As another DEmiRNA, miR-30d was showed to inhibit IBV replication through suppressing ubiquitin-specific protease 47 (USP47) in HD11 (avian macrophage-like cells) cells [121].…”
Section: Ncrnas Involved In Infectious Bronchitis Virus (Ibv) Infectionmentioning
confidence: 98%
“…miRNAs can regulate various aspects of immune response process. In avian, some specific miRNAs were identified to be differentially expressed in many different types of chicken diseases from virus, parasite, and bacteria, such as miR-155 [68,110,141,142], miR-221/222 [60,83,119,138], miR-130 [59,90,109], miR-30 [121,152,155], miR-34 [59,63,132,154,163], let-7 [57,81,155], miR-181 [77,134,155], miR-16 [80,115], miR-455 [125,134,155], etc. It indicated their extensive roles in regulating avian immunity.…”
Section: Ncrnas and Salmonella Typhimuriummentioning
confidence: 99%
“…VP35 is a virus protein of the other highly infectious disease Ebola [31]. HD11, also known as Homeobox protein, is known for regulating infectious diseases such as Avian infectious bronchitis virus (IBV) [32] that is in the coronavirus family. Pulmonary coronavirus infection was grouped in cluster #1 and has the closest associations with gene PTP (protein tyrosine phosphatase), which has been mentioned in SARS-CoV replication inhibition studies [33].…”
Section: Qualitative Evaluationmentioning
confidence: 99%